Philological Translation: Problems and Perspectives (On the Translation of the Old English Paraphrases of Exodus and Daniel into Russian) - Maria V. Yatsenko (Studia Litterarum)
The aim of the essay is to describe the specificity of the so called philological translation as the main technique applied to the translation of the ancient texts into modern languages. The article focuses on the translation of Old English poetic paraphrases of the Bible into Russian. The analysis justifies the necessity of using philological translation to translate such texts. It describes the main stages of translation process as well as the specificity of conveying stylistic peculiarities of the original text, paying special attention to the stylistic effects of the Old English poetry and its counterparts in the Russian verse. The essay stresses the role of the modern perspective and the poetical tradition of the past that should be taken into account by a translator of such texts. The indispensable parts of the philological translation are introductions and extensive commentary on the linguistic, cultural, and religious aspects of the translated texts that provides its better understanding.